Identify Mathematical Gestures of Deaf Students in Solving Mathematics Problems - Heldiana Ferly, Nonny Zakiyanita; Putra, Eric Dwi; Marsidi, Marsidi (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
Gestures that can help students communicate mathematically can be called gestures. This study aims to find out gestures that can help deaf students when solving math problems. This research uses a descriptive approach with a qualitative research type. The data sources used are test questions, observations, and interviews. This research was conducted at SLB ABC Balung with the subject of research as many as 2 SMALB students. The results of this study show that both subjects have their own characteristics when working on the problem. The first student prefers to count using movements assisted by scribbles, while the second student prefers to use hand gestures. In the first student, gestures occurred 38 times, consisting of iconic gestures 17 times, metaphorical gestures 10 times, and deictic gestures 11 times. In the second student, gestures occurred 40 times, consisting of iconic gestures 13 times, metaphorical gestures 5 times, and deictic gestures 22 times. Based on the results of this study, the gesture most often used when deaf students solve the problem is the deictic gesture, which occurs 33 times, and the gesture that appears the least is the metaphorical gesture, which occurs 15 times.